Analisis Kekeringan Pada Daerah Aliran Sungai (DAS) Bedadung Berbasis Sistem Informasi Geografis (SIG) - Ainur Rofiq Kurniawan; M Bisri; Ery Suhartanto (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
The reduced of water availability toward the needs is one thing that indicates the occurrence of a drought. The drought has received more attention from Government of Jember Regency in the form of a drought disaster area management direction. The location of this research is in the Bedadung River Basin with 13 rainfall station located in the upstream of Rowotamtu AWLR Station. Drought analysis uses the Palmer Drought Severity Index method in the form of index that informs the level of drought in an area. The results of the study showed that drought with extreme dry classification occurs from June to October with drought index values ranging from -1,82 (on June) to -14,14 (on October). Patrang, Jelbuk, Arjasa and Panti sub-districts are areas that have experienced drought with a duration of 5 months. Palmer method meteorological drought index and hydrological drought index (value of AWLR Discharge Standardized Box Cox Transformation (Z)) have unidirectional relationship and high degree of relationship, with the Pearson correlation coefficient, r = 0,91